Smart phone and next generation mobile computing - Zheng, Pei, 1972-; Ni, Lionel M. (Amsterdam ; Boston : Elsevier ; San Francisco : Morgan Kaufmann ; Oxford : Elsevier Science [distributor], 2006)
This in-depth technical guide is an essential resource for anyone involved in the development of smart mobile wireless technology, including devices, infrastructure, and applications. Written by researchers active in both academic and industry settings, it offers both a big-picture introduction to the topic and detailed insights into the technical details underlying all of the key trends. Smart Phone and Next-Generation Mobile Computing shows you how the field has evolved, its real and potential current capabilities, and the issues affecting its future direction. It lays a solid foundation for the decisions you face in your work, whether youre a manager, engineer, designer, or entrepreneur. + Covers the convergence of phone and PDA functionality on the terminal side, and the integration of different network types on the infrastructure side + Compares existing and anticipated wireless technologies, focusing on 3G cellular networks and wireless LANs + Evaluates terminal-side operating systems/programming environments, including Microsoft Windows Mobile, Palm OS, Symbian, J2ME, and Linux + Considers the limitations of existing terminal designs and several pressing application design issues + Explores challenges and possible solutions relating to the next phase of smart phone development, as it relates to services, devices, and networks + Surveys a collection of promising applications, in areas ranging from gaming to law enforcement to financial processing.
Introduction to smart phone and mobile computing -- The next wave of computing -- Supporting wireless technologies -- Mobile terminal platforms -- Mobile networking challenges -- Mobile security and privacy -- Mobile application challenges.
Includes bibliographical references and index.
Keywords: Mobile computing; Mobile communication systems; Wireless communication systems; Radiocommunications mobiles; Electronic books